A Clinical Method for Prediction of Alveolar Bone Mineral Density in the Area between the Second Premolar and First Molar in Iraqi Adults with Class I Occlusion - Maha A Al-Juboori; Hadeel A Al-Hashim (College of Dentistry/ University of Baghdad, 2015)
Background: Orthodontic mini-implants are increasingly used in orthodontics and the bone density is a very important factor in stabilization and success of mini-implant. The aim of this study was to observe the relationship among maximum bite force (MBF); body mass index (BMI); face width, height and type; and bone density in an attempt to predict bone density from these variables to eliminate the need for CT scan which have a highly hazard on patient. Materials and Methods: Computed tomographic (CT) images were obtained for 70 patients (24 males and 46 females) with age range 18-30 years. The maxillary and mandibular buccal cortical and cancellous bone densities were measured between 2nd premolar and 1st molar at two levels from the alveolar crest (3 and 6 mm). Face height and width were measured from CT. Clinically; Maximum bite force was measured on first molar region unilaterally by a digital device. The sample was divided into two groups according to the body mass index into; normal and overweight. Results: The results obtained showed that there were no statistical significant differences in MBF or bone density in both genders. Only the cortical bone density in maxilla in overweight group tended to be higher than normal BMI group. The face width and height correlated significantly negatively with MBF which correlated significantly positively with cortical bone density. Conclusions: It was concluded that a prediction of cortical bone density of preselected areas can be made from maximum bite force, body mass index and inter-zygomatic width.